Investigation of LVRT capability of wind driven dual excited synchronous generator. Issue 2 (April 2023) - Yassin, Haitham Mahmoud; Abdel Wahab, Ramadan Ragab; Hanafy, Hanafy Hassan
This paper proposes an effective control technique for low voltage ride through (LVRT) capability in dual excited synchronous generator (DESG) wind turbines. The proposed control technique is dependent on controlling the field circuit parameters. Where the active power is controlled by the field-current space phasor magnitude and the reactive power is controlled by the field-voltage space phasor phase. With the proposed control strategy, the DESG can generate additional reactive power to support grid voltage recovery under grid faults. The DC-link voltage is kept within an acceptable limit since the excess power, due to the power mismatch between the mechanical and armature power is stored in the generator inertia. Using the proposed control strategy, the DESG can enhance the LVRT capability efficiently without using extra protection circuits or any additional control techniques during fault conditions. To test the proposed control method, simulation, and experimental results for a 1.1 kW DESG wind turbine system were obtained.